KEMAMPUAN KOMUNIKASI MATEMATIKA SISWA SMP DALAM SETTING PEMBELAJARAN RME (REALISTIC MATHEMATICS EDUCATION) (Universitas Negeri Semarang, 2013)
Penelitian ini bertujuan untuk memperoleh gambaran tentang komunikasi matematik siswa dalam setting pembelajaran RME. Subyek penelitian ini adalah siswa kelas 2 SMP di Kota Semarang. Data diperoleh dari hasil kerja siswa dalam menyelesaikan masalah kontekstual pada pokok bahasan perbandingan dan pokok bahasan sistem persamaan linier dengan dua peubah. Hasil kerja siswa tersebut dikategorikan dalam 5 level (terendah level 0 dan tertinggi level IV). Untuk pelevelan peneliti mengembangkan rubrik skoring komunikasi matematika dengan merujuk pada Quantitative criteria for scoring mathematical communication. Data hasil skoring dianalisis secara deskriptif-kuantitatif. Hasil pelevelan dalam komunikasi matematik adalah: untuk pokok bahasan Perbandingan: level I 78 %, level II 15 %, level III 5%, level IV 2%. Sedangkan untuk pokok bahasan Sistem Persamaan Linier dengan Dua Peubah: level I: 67 %, level II: 18 %, level III: 8%, level IV: 7%. Purpose of this research is to describe about mathematics communication in RME setting of junior school student. Subject of the research were grade 8 students in Semarang City. Data obtained from the student's work in solving contextual problems on the subject of the Ratio and the subject of System of Linear Equations with Two Variables. The student's work is categorized into 5 levels (the lowest level (0) to the highest level (IV)). For leveling researchers developed a scoring rubric with reference to the communication of mathematics quantitative criteria for scoring mathematical communication. Data were analyzed descriptively-quantitative. The work of students was also analyzed qualitatively by referring to Qualitative Analytic Scoring Procedure for communication of mathematics. The results can be expressed are: for subject ratio: 78% level I, level II, 15%, 5% level III, level IV 2%. As for the subject of Systems of Linear Equations with Two Variables: level I: 67%, level II: 18%, level III: 8%, level IV: 7%. Both of subject in level V were not achieved.